Téa Obreht’s Transnational Disremembering within the Mythical Realism of The Tiger’s Wife - Selma Raljević ([sic])
This paper discusses Téa Obreht's 2010 novel The Tiger's Wife within the context of transmigrations and post-national conceptions of both the real and mythical translocality. Through analysis of Obreht’s discourse of disremembering, which is in Aleksandar Hemon’s definition a recognition of one’s own experience under the new narrative, the paper will explore the transnational dimensions of the Slavic-American identity of The Tiger’s Wife. The aim of this paper is to focus on the new understanding of transnational relationality as well as on a reconception of reality that disremembers Obreht’s or, on a larger scale, human experience within the mythical realism of The Tiger’s Wife.Keywords: transnationalism, the Slavic-American identity, disremembering, Aleksandar Hemon, Téa Obreht, The Tiger’s Wife, mythical realismTo disremember, according to Aleksandar Hemon, a celebrated Bosnian-American writer with an immigrant experience, is to recognize one’s own experience under the new narrative. He points out that it especially refers to the “people who have come through a form of actual, physical slaughter, and to the extent the construction of narrative is memory, then the narrative, for them, has to involve a quantity of amnesia. More amnesia that is involved in most narrative” (Interview by Richard Wirick). Disremembering blends non-fiction and fiction, genocide documentation and utopian imagery, and implies an alternative interpretation of reality. Hemon’s 2008 novel The Lazarus Project is a transnational project of disremembering. In The Lazarus Project, Hemon intertwines a double narrative of the multilayered parallel universes of the past and the present by following the narrator Vladimir Brik, a post-war Bosnian who lives in the United States, as he questions his life. Brik traces the story of Lazarus Averbuch, a young Jewish immigrant who is a survivor of the Kishinev pogrom in what is now Moldova, and an alleged anarchist. At the same time, Brik questions both the inner and outer aspects of his reality. In the first-person narrative, he explains that he needs to re-imagine what he could not retrieve, and to see what he could not imagine. For this reason, he disremembers his own experience within the story of Lazarus that also implies resurrection and a new birth story. This paper will analyze Téa Obreht’s evocative 2010 novel The Tiger's Wife from the point of view of a Hemonesque narrative concept of disremembering and, within the discourse, an Obrehtesque interaction of myth and truth.